FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUNTARY AUDITOR SWITCHING (STUDI EMPIRIS PADA PERUSAHAAN NON FINANCING YANG TERDAFTAR DI BURSA EFEK INDONESIA ) - Audrey Siahaan; Dame Ria R. Saragi (Visi Sosial Humaniora, 2020)
The phenomenon of Auditor switching has been found to have implications for the credibility of a financial report's value and the monitoring costs of management activities. This study's sample was non-financing companies, which were listed as issuers on the IDX during the 2017-2018 period. Change of Management and company growth together did not affect voluntary Auditor switching. Audit delay does not affect voluntary Auditor switching. The evolution of management does not affect voluntary Auditor switching. Company growth does not affect voluntary Auditor switching.